Síntese de nanopartículas de prata suportadas em microesferas e filmes de quitosana: estudo da atividade antibacteriana e aplicação na liberação controlada de ibuprofeno - Pereira, Anna Karla dos Santos (Universidade Federal do Tocantins, 2017)
Since the 1990s studies related to chitin and chitosan polymers have been stimulated. The presence of more NH2 groups in chitosan allows its application as an efficient biomaterial without drug loading and adsorption of metallic cations. In this work, chitosan films and microspheres were made for use in silver ion adsorption procedures, drug release and antibacterial activity. The polymer showed a degree of deacetylation corresponding to 81% and zero loading point at pH ~ 7. As obtained microspheres had a mean diameter of 2911 mm and a standard deviation of 0.325, when used. The use of chitosan in the form of microspheres and films provides an increase of the surface area, besides facilitating the handling of the polymer. The films were formed with single step silver nanoparticles. The best pH for the Ag+ ion adsorption study in the aqueous medium is in the pH range of 5 to 7, the best fit for the Langmuir model, the optimal time for the maximum adsorption of 10 hours and the apparent energy value of adsorption (E) of 6,9 kJ / mol, which characterizes it physical adsorption. The study of ibuprofen release was performed in simulated gastric fluid and simulated intestinal fluid, further release of the drug occurs no neutral pH of intestinal fluids. Transdermal delivery of drug by films was performed at pH = 7.4 to simulate blood tissue and the apex of ibuprofen release occurred early in contact with the simulated fluid material. As microspheres and films with silver nanoparticles they demonstrate activity against E. coli and S. aureus.